Fly on the Wall: Using Teleconferencing to Supervise Student Teacher Performance - Marcia Bolton (Flexible Learning Association of New Zealand, 2011)
The use of teleconferencing between a rural state college supervisor and her professional development school partners has added a new component to the mission to educate teachers of the 21st century and to create a learning community in a remote school location. Supervising student teachers by teleconference has increased the college's potential for preparing teachers who are in tune with the most advanced types of instruction in our Professional Development Partnership with Calhoun County Schools, USA.